Posterior Ligamentum Complex Preservation Alleviate ASD‐Related Biomechanical Deterioration in Lumbar Interbody Fusion Models: A Finite Element Analysis - Lipeng He; Tingchen Zhu; Weiye Cai; Wenhao Yang; Zan Chen; Jingchi Li (JOR Spine)
ABSTRACT Background There are differences in the extent of excision of articular processes, spinal processes and posterior ligamentum complexes (PLC) for posterior approach lumbar interbody fusion. Given that the biomechanical significance of these structures has been verified and that deterioration of the biomechanical environment is the main trigger for complications in both fused and adjacent motion segments, changes in decompression ranges may affect the potential risk of adjacent segmental disease (ASD) biomechanically; however, this topic has yet to be identified. Methods Posterior lumbar interbody fusion (PLIF) with different decompression strategies was simulated in a well‐validated lumbosacral model. The excision and preservation of the cranial motion of the segmental PLC and the lateral articular process in the fusion segment were simulated in this model. The stress distribution in the cranial motion segment was computed under different loading conditions to determine the potential risk of ASD. Results Compared to complete bilateral articular process excision, preservation of the lateral two‐thirds of the articular process did not alleviate stress concentration on the cranial motion segment both in PLC preserved and excised models. In contrast, preservation of the cranial segmental PLC can obviously alleviate the stress concentration tendency of the cranial intervertebral disc under flexion loading conditions. Conclusion Preservation of the lateral parts of the articular process cannot optimize the biomechanical environment, in contrast, PLC preservation can effectively alleviate ASD related biomechanical deterioration of the cranium segment.